An Update on the Anticancer Activity of Xanthone Derivatives: A Review - Yehezkiel Steven Kurniawan; Krisfian Tata Aneka Priyangga; Jumina; Harno Dwi Pranowo; Eti Nurwening Sholikhah; Abdul Karim Zulkarnain; Hana Anisa Fatimi; Jeffry Julianus (MDPI AG, 2021)
The annual number of cancer deaths continues increasing every day; thus, it is urgent to search for and find active, selective, and efficient anticancer drugs as soon as possible. Among the available anticancer drugs, almost all of them contain heterocyclic moiety in their chemical structure. Xanthone is a heterocyclic compound with a dibenzo-γ-pyrone framework and well-known to have "privileged structures" for anticancer activities against several cancer cell lines. The wide anticancer activity of xanthones is produced by caspase activation, RNA binding, DNA cross-linking, as well as P-gp, kinase, aromatase, and topoisomerase inhibition. This anticancer activity depends on the type, number, and position of the attached functional groups in the xanthone skeleton. This review discusses the recent advances in the anticancer activity of xanthone derivatives, both from natural products isolation and synthesis methods, as the anticancer agent through in vitro, in vivo, and clinical assays.